2020
DOI: 10.1016/j.ijwd.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Menses, pregnancy, delivery, and menopause in hidradenitis suppurativa: A patient survey

Abstract: Background Hidradenitis suppurativa (HS) is a chronic inflammatory disorder that primarily affects women of childbearing age. There is a paucity of data on HS disease activity during menstruation, pregnancy, and menopause and the potential impact of HS on the method of delivery. Objective We aimed to characterize the natural history of HS symptoms during menses, pregnancy, and menopause. We also sought to evaluate the potential impact of HS on delivery method and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 8 publications
0
31
0
4
Order By: Relevance
“…Clinicians should also consider that women with painful menstrual periods and menstrual migraines may take non-steroidal anti-inflammatory drugs (NSAIDs), a possible trigger factor in HS. So, treating this syndrome with OCPs may remove these symptoms and decrease the menstrual use of NSAIDs and HS exacerbation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should also consider that women with painful menstrual periods and menstrual migraines may take non-steroidal anti-inflammatory drugs (NSAIDs), a possible trigger factor in HS. So, treating this syndrome with OCPs may remove these symptoms and decrease the menstrual use of NSAIDs and HS exacerbation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pregnant women with HS should also receive appropriate counseling with regard to appropriate weight gain during pregnancy ( Fernandez et al, 2020 ). This is based on the association of increased body mass index with a risk of developing HS, although the exact mechanisms are incompletely understood.…”
Section: Pregnancy and Hidradenitis Suppurativamentioning
confidence: 99%
“…It is also vital that the woman is referred to various appropriate medical and allied health care teams. It has been widely demonstrated that integrated multidisciplinary management of patients with HS improves patient outcomes and satisfaction with care ( Fernandez et al, 2020 ; Touhouche et al, 2020 ).
Fig.
…”
Section: Pregnancy and Hidradenitis Suppurativamentioning
confidence: 99%
“…This study also showed that HS may affect delivery methods, because physicians reportedly advised patients with severe anogenital HS to have Cesarean sections as opposed to vaginal deliveries (Fernandez et. al, 2020 ). However, more than half of patients who had Cesarean sections reported new HS lesions in the incision scar Collier et al, 2021 .…”
mentioning
confidence: 95%
“…Does hormonal HS warrant consideration as a subtype of HS? Fernandez et al (2020) contributed significantly to this discussion by characterizing HS in female patients in various stages of life. The study revealed that menstruation caused worsening of HS symptoms in 76.7% patients, pregnancy had mixed effects, and menopause typically caused no change or worsening of HS symptoms.…”
mentioning
confidence: 99%